2016
DOI: 10.1166/jnn.2016.12309
|View full text |Cite
|
Sign up to set email alerts
|

Cytocompatibility of HeLa Cells to Nano-Sized Ceramics Particles

Abstract: In this study, we investigated the behaviors and cytocompatibility response of human cervical carcinoma (HeLa) cells expose to nano-sized particles. Cultivated cells exposed to titanium oxide and indium oxide nanoparticles remained highly viable. In the presence of copper oxide (CuO); however, the cells became seriously inflamed. To understand the mechanism by which CuO causes cell death, we evaluated cell death and apoptosis cytometry. CuO induced cells apoptosis more strongly than exposure to titania nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Therefore, the CuO particles affected the cells because of their interaction with the surface caused by the contact. In a previous study, it was reported that CuO exposure induced apoptotic cell death in Hella cells [11]. Karlsson reported that CuO nanoparticles showed cytotoxicity by causing oxidative lesions and increasing intracellular reactive oxygen species [5].…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, the CuO particles affected the cells because of their interaction with the surface caused by the contact. In a previous study, it was reported that CuO exposure induced apoptotic cell death in Hella cells [11]. Karlsson reported that CuO nanoparticles showed cytotoxicity by causing oxidative lesions and increasing intracellular reactive oxygen species [5].…”
Section: Resultsmentioning
confidence: 98%
“…Some studies have reported that cancer cells such as HeLa cells and human lung cancer cells (A549) were used to evaluate cell compatibility. When the materials show low cytotoxicity to cancer cells, they also have cell compatibility with normal cells. The cytotoxicity of the quaternized alginate-based copolymer was tested against normal cells and HeLa cells in our previous work, which shows that quaternized alginate-based copolymers have good biocompatibility for both cells. The CCK-8 method was used to explore the cytotoxicity of the QSA 769 - g 485 -(EOX) n copolymer brush against HeLa cells, and the experimental results under concentration from 20 to 500 μg/mL are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%